An unusual variant of lipoma: case report. Issue 5 (18th May 2022) - Elouarith, Ihssan; Elmajoudi, Salma; Habiba, Kadiri; Ech-charif, Soumaya; Mahdi, Youssef; Khmou, Mouna; El khannoussi, Basma
Abstract: Osteo-lipoma is a very rare benign tumor with a good prognosis. It is composed mainly of mature fatty tissue with a bony component. The diagnosis is based on the histological study, given the clinical and radiological characters that can simulate other benign or malignant pathologies. Osteosarcoma is the main differential diagnosis. The distinction between these two neoplasms is essential as the basis of the treatment is different. We report the case of a patient with a giant ossifying lipoma independent of bone tissue located in the thigh.